2018
DOI: 10.3390/recycling3030037
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of the Physical and Combustion Properties of Briquettes Produced from Agro-Wastes and Wood Residues

Abstract: This study investigated the physical and combustion properties of briquettes produced from agricultural wastes (groundnut shells and corn cobs), wood residues (Anogeissus leiocarpus), and mixture of the particles at 15%, 20%, and 25% starch levels (binder). A 6 × 3 factorial experiments in a Completely Randomized Design (CRD) was adopted for the study. The briquettes produced were analyzed for density, volatile matter, ash content, fixed carbon, and specific heat of combustion. The result revealed that the den… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 10 publications
3
32
1
5
Order By: Relevance
“…This is within 0.4-1.8% for pure wood, 6.3-10.4% for wood bark, 2.4-7.7% for energy crops, 6.9-9.2% for agricultural biomass and 1.1-9.2% for waste from the production of plant-based food [12]. Falemara et al [13] obtained an amount of ash between 3.4-4.9% for briquette from peanut shells, maize cobs and Anogeissus leiocarpus. James et al [6] found that the typical amount of ash produced was 1.2% for pine wood, 1.0% for willow wood, 0.8% for birch wood, 12.9% for Miscanthus, which was much greater, 9.3% for rice pellets, 16.3% for rice husks and 5-10% for agricultural crop materials.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…This is within 0.4-1.8% for pure wood, 6.3-10.4% for wood bark, 2.4-7.7% for energy crops, 6.9-9.2% for agricultural biomass and 1.1-9.2% for waste from the production of plant-based food [12]. Falemara et al [13] obtained an amount of ash between 3.4-4.9% for briquette from peanut shells, maize cobs and Anogeissus leiocarpus. James et al [6] found that the typical amount of ash produced was 1.2% for pine wood, 1.0% for willow wood, 0.8% for birch wood, 12.9% for Miscanthus, which was much greater, 9.3% for rice pellets, 16.3% for rice husks and 5-10% for agricultural crop materials.…”
Section: Introductionmentioning
confidence: 76%
“…The amount of ash produced from biomass was higher than noted in wood, but lower in comparison to agricultural crops. This situation can be related to the quality and origin of the material [13,42]. In the experiment the pellet made of wood without the bark and straw material was used.…”
Section: Characteristics Of Biomass Pelletsmentioning
confidence: 99%
“…The authors reported a higher briquette density with an increase in applied pressure and also a higher heating value as the particle size increased. Falemara et al [20] experimentally studied briquettes prepared from groundnut shell, corn cobs, and wood residues with starch as the binder. They used different mixture strengths of raw materials for preparing the briquettes.…”
Section: Prasityousil and Muenjinamentioning
confidence: 99%
“…There are also descriptions of problems encountered while using biomass heating furnaces, especially such as disturbances in the use of furnaces due to corrosion of mechanisms, formation of slags that are difficult to remove, and disturbances of combustion control [3,6,[19][20][21][22][23]. One of the reasons for the abovementioned problems is the presence of aggressive chemical compounds formed during the combustion of biomass and other fuels, as well as those that are not environmentally neutral.…”
Section: Introductionmentioning
confidence: 99%
“…According to Febrero et al [29], even a low Cl content in biomass can lead to serious furnace damage. In the cited standards, there are also limits on the N and S content, i.e., elements leaving the furnace as N 2 , acid anhydrides, NO x , and SO 2 (according to different indications, <0.3% for N and <0.04-0.08% (0.5)% for S) [19]. According to Obernberger [28], furnace damage occurs when the content of S in the fuel is >0.2%.…”
Section: Introductionmentioning
confidence: 99%